1985
DOI: 10.1093/nar/13.24.8999
|View full text |Cite
|
Sign up to set email alerts
|

Xenopusribosomal gene enhancers function when inserted inside the gene they enhance

Abstract: The ribosomal DNA of Xenopus laevis contains repeated sequence elements in the intergenic spacer region that enhance transcription from the adjacent gene promoter (1,2). Previous work has shown that these RNA polymerase I enhancers influence the target promoter when they are in either orientation, at a distance of several kilobases, and only when they are in cis (3-5). In this work, we further show that enhancer activity is unaffected by inserting the enhancers within the transcription unit whose promoter is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…3, lane 2, the fragment encompassing -980 to -245 did not decrease the T2 signal (compared with the results of the control plasmid in lane 6) and thus had no terminator activity. This result confirmed our earlier report that the enhancer elements do not stop RNA polymerase (9) and located the termination activity to between -245 and -123. Testing several 3' deletions of this region, we found that the region from -245 to -190 still supported termination in this assay (lanes 3 through 5) but that a further 3' deletion to -206 abolished the termination activity (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3, lane 2, the fragment encompassing -980 to -245 did not decrease the T2 signal (compared with the results of the control plasmid in lane 6) and thus had no terminator activity. This result confirmed our earlier report that the enhancer elements do not stop RNA polymerase (9) and located the termination activity to between -245 and -123. Testing several 3' deletions of this region, we found that the region from -245 to -190 still supported termination in this assay (lanes 3 through 5) but that a further 3' deletion to -206 abolished the termination activity (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Our results from the direct cis stimulation assay (Fig. 3) showing that enhancement by the 60/81-bp repeats is very position dependent refute prior assertions (26,27,42,44) that the 60/81-bp repeats augment transcription equally when located far upstream of the initiation site or when downstream of the initiation site within the transcribed region. These earlier conclusions derived from results obtained with trans competition assays, in which the relative amount of transcription 50-Sg/ml concentration of each of the indicated pairs of plasmids, and transcription was assessed by Si mapping, using the A probe (which hybridizes specifically to transcripts of the A-gene family) and the B probe (which hybridizes specifically to transcripts of the B-gene family).…”
supporting
confidence: 85%
“…The widely accepted view is that the 60/81-bp elements also stimulate transcription from an rDNA promoter in cis and that this stimulation is orientation-and position-independent enhancement (42,44), occurring equally efficiently when the repeats are kilobase pairs distant from the promoter and when they are downstream of the promoter within the transcribed portion of the template (26,27,44,47). These conclusions are based almost entirely on oocyte coinjection experiments using two competing, promoter-bearing templates (13,26,27,45,47); when one also carries the 60/81-bp repeats, the transcriptional balance is shifted toward that promoter and away from the one lacking the repeats (such an assay is illustrated in Fig. 4A, lanes 1 to 3 with two marked rRNA genes).…”
mentioning
confidence: 99%
“…It is useful to compare the enhancer described above with the 60-to 81-bp repeats that have enhancer activity for rRNA transcription in Xenopus oocytes and which also work from upstream of two genes or between two genes (22,23). The two enhancers differ in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…Within them are found a variety of sequence elements that influence the level of transcription. In Xenopus laevis, for example, these include several copies of a sequence closely related to the promoter, dubbed spacer promoters (6,7,22,23,29,33), each followed by about 10 copies of a 60-to 81-base-pair (bp) repeat, that behave in some respects like enhancer elements (22,23,29). The spacer promoters are curious because although they can give rise to transcripts and can stimulate transcription from an adjacent real promoter (6,7,29), the transcription from the spacer promoter seems not to be involved in this stimulation (7,25).…”
mentioning
confidence: 99%